The Development of Online Integrated Competency Test Material to Improve Graduate Competency (Journal of Vocational and Career Education, 2022)
Vocational High School is an institution that prepares skilled workers. The National Education System Law states that competency certificates are given by education and training institutions to participants as an acknowledgment of their competence, administered by an accredited education unit or certification institution. The selection of this scheme can increase the graduate competency significantly. The present study aims at simplifying and improving graduate competency. The instrument used in the present study is an assessment sheet on the website media of the Level II Certification scheme from 7 clusters to 40 units; and a questionnaire to measure the graduate competence of grade XII TKR students at SMK Negeri 1 Semarang. The data analysis used in this research is categorical to determine the level of feasibility of the website media for the Level II Certification scheme from 7 clusters to 40 units; and N-Gain and the different N-Gain test using the t-test, to determine the effectiveness of the website media for the Level II Certification scheme from 7 clusters to 40 units on the graduate competency. Based on the feasibility test and the effectiveness test according to the responses given by the experts, the criteria for the responses were very feasible. From the effectiveness test in the experimental class, the module obtained quite effective and significant criteria used by students to improve the graduate competence.